The Role of Maladaptive Daydreaming on Celebrity Worship Syndrome - Andhila Sasadara Krisnanda; Nida Ul Hasanat (Schema: Journal of Psychological Research, 2025)
Celebrities exert a significant influence on individuals' daily lives. The phenomenon of celebrity worship encompasses admiration, devotion, and emotional attachment towards public figures. When this attachment becomes excessive, it may develop into Celebrity Worship Syndrome (CWS), associated with adverse psychological outcomes. This study investigates the role of maladaptive daydreaming in predicting the intensity of celebrity worship. A total of 184 emerging adults aged 18 to 33 years in Indonesia, all self-identifying as fans of their favourite celebrities, participated in this research. Utilising a quantitative approach, data were collected through an online survey disseminated via various social media platforms. Linear regression analysis revealed that maladaptive daydreaming significantly predicted levels of celebrity worship, accounting for 23.6% of the variance. These findings underscore the psychological implications of immersive fantasy in fan behaviour and highlight the need for further exploration of maladaptive daydreaming within the cultural context of Indonesian society.